Laura Gosalbo & Henri-Pierre Millescamps: Celebrity Chefs. Food Entertainment History - Hayward, Vicky (Petits Propos Culinaires, 2012)
Laura Gosalbo & Henri-Pierre Millescamps: Celebrity Chefs. Food Entertainment History: Gastronomía Activa, 2009, 455 pp., hardback, €50.